2011
DOI: 10.1149/1.3567762
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electrodeposition of CuInSe2 Thin Films onto Mo-Glass Substrates

Abstract: In this study, copper indium selenide (CIS) films were deposited by pulsed electrodeposition with multi potentials to control the atomic ratio of the CIS film and improve the deposition uniformity. It was found that smaller duty cycle and pulsed period enhanced the cathodic current due to ion replenishment. The results show that the Cu=In ratio was significantly influenced by reverse voltage of pulsed electrodeposition. The uniformity of the CIS films can be improved by proper reverse voltage. The deposition r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Murali et al prepared CIS thin-films using pulse electrodeposition with varied duty cycle from 6 to 50% and reported the p-type phase pure CIS films with resistivities in the range of 1-10 ohm-cm [64]. Hu et al employed the deposition of CIS films by pulse electrodeposition wherein multi potentials were used to control the composition of the films which resulted in improved deposition uniformity without any secondary phases [65]. Similar reports on the compositional control of CIS thinfilms by the variation of pulse parameters have appeared in the recent past [66][67][68][69].…”
mentioning
confidence: 99%
“…Murali et al prepared CIS thin-films using pulse electrodeposition with varied duty cycle from 6 to 50% and reported the p-type phase pure CIS films with resistivities in the range of 1-10 ohm-cm [64]. Hu et al employed the deposition of CIS films by pulse electrodeposition wherein multi potentials were used to control the composition of the films which resulted in improved deposition uniformity without any secondary phases [65]. Similar reports on the compositional control of CIS thinfilms by the variation of pulse parameters have appeared in the recent past [66][67][68][69].…”
mentioning
confidence: 99%
“…The effect of using different E 2 values was out of the scope of this study, although it was found that E 2 positive to 0.0 V resulted in film detachment. This variable has been investigated by Hu et al [13], who showed that the Cu/In ratio was influenced by changing the reverse voltages. The duration of each potential step was 10 s for both, E 1 and E 2 , resulting in a duty cycle of 50 %.…”
Section: Electrochemical Techniques and Electrodeposition Of Cuinse 2...mentioning
confidence: 99%
“…For pulsed electrodeposition, there are a few articles where the mechanistic aspects have been discussed [12,13]. Considering the profile of the alternating signal imposed on the electrode, it can be expected that the experimental parameters (such as substrate and electrolyte composition, potentials, and times among others) will play a different role in the mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…By limiting the amount deposited using the time for the cathodic pulse, PP-ALD avoids burying any elemental excess as it remains accessible to stripping during the anodic pulse. CuInSe 2 (CIS) is a highly stable, chalcopyrite semiconductor with potential applications in p-type photovoltaics, light-emitting diodes, optoelectronics, and nonlinear optical devices. , CIS has a direct bandgap around 1.08 eV , and a high absorption coefficient ( a ∼ 10 5 cm –1 ) leading to laboratory efficiencies as high as 15%. , CIS has been formed using techniques such as coevaporation; flash evaporation; chemical vapor deposition; chemical spray pyrolysis; , chemical synthesis; selenization of sputtered, evaporated, or electrodeposited Cu and In stacked layers; electrochemical codeposition; and pulse electrodeposition. ,,, …”
Section: Introductionmentioning
confidence: 99%